To study the variation in growth of Aspergillus and Trichoderma strains under the effect of metal ions, pH, temperature and solvents - Singh, Alvina; Chaturvedi, Rachna; Singh, Sujeet Kumar (Research in Biotechnology, 2014)
The fungal strains isolated in the current work are Aspergillus and Trichoderma, these strains are commonly found in soil have different tolerance for different metal ions and solvents. Physiological conditions like pH and Temperature were also varied to check the maximum activities of these fungal strains. The maximum inhibition zone for metal ions was of Aspergillus by zinc ions while of Trichoderma by calcium ions. Normally, we culture fungal strains at pH 7.3 but after the study of optimization of the culture conditions at various pH, the fungal strains can grow at other pH as well. The maximum growth kinetics of Aspergillus was at pH 11 while of Trichoderma was at pH 3 apart from pH 7. The Tolerance of Aspergillus for solvents was found to be maximum by ethanol while of Trichoderma the maximum Tolerance by propan-2-ol.